Micropropagation of Azadirachta indica and assessment its fungicidal action - Priya R Iyer*, Regin Susan Abraham and (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">An effective protocol has been developed for micropropagation of Azadirachta indica using <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-GB">Murashige and Skoog (<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> MS) medium supplemented with different hormones likeÃ‚Â Ã‚Â Ã‚Â 1-Naphthyl acetic acid(NAA),3-Indole acetic acid(IAA),3-Indole butyric acid(IBA),6 Benzyl aminopurine (BAP),2,4- dichlorophenoxyacetic acid(2,4-D)and Kinetin.Ã‚Â Extracts obtained were analyzed using HPTLC. Different sample preparations were compared for action against fungi like Aspergillus niger, Penicillium sp, Aspergillus versicolor, Drechslera sp with sample from the original plant. <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-GB">The present in vitro procedure is more effective than the conventional techniques used in conservation and mass propagation of this <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">medicinal <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-GB">plant.